Students’ Perception of Speaking Practice In Step Up English Club at Ho Chi Minh City University Of Technology and Education - Nguyễn Thị Nhã Quỳnh (Indonesian Journal of Educational Research and Technology, 2021)
English club was a club of students with common ambitions or interests in English. This study aims to find out Students’ Perceptions of Speaking Practice in the Step-Up English Club (SU) club. This study used the qualitative method, observation, and interview as research instruments. The subject of this study is the members of the SU club as participants. As the result of interviews, most of the students had positive perceptions about joining in SU club, yet some still haven't adapted to the online meetings. The students believe that SU clubs could improve their fluency. The student also had a perception through an English meeting club as a proper environment to enhance skills especially in speaking. There are similarities between this research and the previous research. English meeting clubs have a positive influence on learning English. However, there are some different results found, especially from the social distancing time during Covid 19 pandemic. Positively, with both online meetings and offline meetings, the SU Club gives students a place to properly practice speaking English without fear to make mistakes and is an appropriate medium to improve students' speaking skills. However, English clubs, in general, should design more diverse and fun activities, to gradually change students' reluctance to take online sessions.